Collaborative logistics: a study among small and medium sized supermarkets and their suppliers - Vieira, José Geraldo Vidal; Machado, Vitor Rocha (Revista Gestão da Produção Operações e Sistemas, 2008)
In recent years, the supermarket sector has undergone several changes, especially related to the relationshipamong its members, when searching for collaborative logistics. This research characterized the logistics structureof small-size supermarkets in Minas Gerais, Brazil, and it evaluated the level of collaboration and the logisticsperformance of its suppliers by means of exploratory and descriptive techniques and uni and multivariateanalysis. One may conclude that logistics collaboration is still found in an initial stage and furthermore, thelogistics performance is considered to be satisfactory by the retailersKeywords: Collaborative logistics, Logistics performance, Retail business.